Association of Learners Academic Performance with the Preparedness and Competence in the Implementation of Modular Learning Among Secondary School Teachers at Lanao del Norte - Pangandaman, Janisa I. (Journal of Basic Education Research, 2023)
Purpose of the study: Part of the challenge in the paradigm shift of the Philippine education system during the pandemic is the adoption and implementation of modular learning in pursuit of the continuity of learning and the promotion of learners' academic performance. This study inquired about the secondary school teachers' preparedness and competence in implementing modular learning and its relationship to learners' academic performance. Methodology: Descriptive correlational approach with triangulation. A stratified sample of secondary school teachers (n = 77) and students (n = 322) was calculated through Raosoft, representing the two national high schools at Lanao del Norte that participated in the researcher-made validated and reliable tool (α = 0.81). Quantitative data were analyzed and yielded mean, frequency, percentage distribution, and Pearson results. Qualitative data were then manually coded, transcribed, and translated. Main Findings: The secondary school teachers are well-prepared to implement modular learning in printing, segregating, delivering, retrieving, facilitating learning, and feedbacking (WM = 3.72). They are generally competent teachers based on their specialization in monitoring, assessing, and evaluating their students (WM = 3.86), with average academic performance (MS =83.03). The secondary school teachers' preparedness (r = -0.19; p = 0.00) and competence (r = -0.30; p = 0.00) significantly correlate with learners' academic performance. Novelty/Originality of this Study: This study conveys the situation of teachers' preparedness and competence in implementing modular learning to promote academic performance despite the challenging situations in the COVID-19 pandemic. It contributes to a better understanding of promoting quality education amid a crisis.